Note from the Editor-in-Chief - Subramanyan, Vighnesh (Consilience, 2012)
Dear Readers, It is my pleasure to present you Issue 7 of Consilience, which our team has been diligently compiling and editing through the Fall of 2011. The wide range of topics and perspectives that this issue brings to the table, now more than expected of a Consilience publication, stretch from microfinance credit-scoring models in West Africa to the viability of hydropower in the Mekong basin to algal blooms in Guatemala. We have endeavoured to form more and deeper connections with academic institutions and networks around the world dealing with sustainable development issues. For example, Liana Ricci, from the Sapienza University of Rome, writes a thought-provoking article on peri-urban development in Tanzania, the submission a result of the collaboration between Consilience and the International PhD Workshop in Sustainable Development, hosted at Columbia University. Critically, Liana’s article points to the fact that more than ever we need to be concerned with institutional capacity building in developing countries. Aspects of this challenge are explored by several of our authors, including Esohe Odaro in her piece on service delivery in Sub-Saharan Africa. Yet it is important to note that sustainable development is not just a concept to be applied to developing countries by those in developed countries, but should be used to critically analyze the current situation and trajectory of the developed world as well. To this aim I am pleased to recommend Frank Hemmes et al’s scholarly article regarding energy use monitoring in the Netherlands, as well as Julia and Robert Fredenburg’s incredibly evocative photo essay regarding river deltas in California. As always, I encourage you to contact me at vs2299@columbia.edu orcontact@consiliencejournal.org with any comments or queries, and I encourage you to continue engaging with us. Enjoy the issue! Vighnesh Subramanyan Editor-in-Chief Consilience: The Journal of Sustainable Development January 17th, 2012